Andhari Tiger Sanctuary (Maharashtra) : a Case for People's Participation in the Management of Protected Areas - Ghate, Rucha (Indian Forester, 1998)
Several attempts of protecting surrounding forests have been made. There is need for peoples participation in management of the protected areas through eco-development programmes by developing sense of mutual trust and understanding, so that the ecological and social objectives could be achieved.